Balancing Tradition and Modernity: The Role of Aqidah Education Management in Shaping Santri Character - Imdad, Muhammad; Hafidhuddin, Didin; Arif, Syamsuddin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the role of aqidah education management in building the character of students in Islamic boarding schools (pesantren), with a focus on strategies and policies implemented to address the challenges of modern education. Amidst the challenges of Islamic education in balancing traditional religious teachings with modern academic demands, this study examines how a holistic approach to curriculum integration, the role of caregivers, and technological advancements can influence student development. This study uses a qualitative case study, with observation, interviews, and documentation for data collection. The findings indicate that the curriculum integration model effectively blends Islamic teachings with modern subjects, thus promoting the holistic development of students. Caregivers play a crucial role in fostering academic and moral growth, creating a supportive and conducive environment that encourages character development. Technological advancements, such as the use of YouTube and online learning media, increase learning flexibility and student engagement. This study contributes to the understanding of how Islamic boarding schools can adapt traditional educational practices to contemporary needs, offering a balanced approach that integrates faith and reason. This study recommends that Islamic boarding schools continue to refine their curriculum integration models and embrace technological tools to further improve student learning outcomes.